Walka o przywództwo w PZPR w roku 1981 w dokumentach aparatu władzy Niemieckiej Republiki Demokratycznej - Gańczak, Filip (Pamięć i Sprawiedliwość, 2014)
The August Agreement of 1980 and the creation of free trade unions in Poland caused anxiety among leaders of the Socialist Unity Party of Germany (SED). The development in the neighbouring People’s Republic of Poland had significant impact on the geopolitical environment of the communist German Democratic Republic. The leader of the SED and the GDR head of state, Erich Honecker, strongly supported the idea of a Warsaw Pact invasion of Poland. However, other East European communist rulers were not willing to go that far, at least in the short term.Under these circumstances, East German authorities tried to influence the leaders of the Polish United Worker’s Party (PZPR), Poland’s ruling communist party, and urged them to impose countrywide martial law. They pinned their hopes on general Wojciech Jaruzelski, who was designated prime minister in February 1981. However, Honecker soon became disappointed and came to the conclusion that new leadership in Poland was necessary.At that time, SED apparatchiks and East German diplomats held many talks with their PZPR colleagues, including local leaders, members of the Central Committee and even the Political Bureau. Following on from this, those among the Polish communists unhappy with the hesitant policy of their leader Stanisław Kania were encouraged to seek for a new leadership. Honecker hoped that, at its eleventh plenary session in June 1981, the PZPR Central Committee would overthrow Kania and bring about political change in Poland. This calculation failed and in July, Kania was even re-elected party leader at the ninth PZPR congress.No change in the politics of Poland seemed possible without Jaruzelski, the head of the army and still a popular figure. In the early Autumn of 1981, GDR authorities received hints that Jaruzelski no longer supported Kania and had become more willing to impose martial law. Kania’s opponents among the Central Committee, strongly supported by the SED and the Soviets, finally managed to oust him from power in October 1981. The Committee appointed Jaruzelski its new First Secretary. Less than two months later, martial law was imposed in Poland. From Honecker’s perspective, his minimum goal was reached.